Penjelasan dengan langkah-langkah:
y = 2x² - 3
x = 1 sampai dngn x = 3
[tex]\sf\int \limits_{1}^{3}(2 {x}^{2} - 3) dx\\ [/tex]
[tex] \sf = \frac{2}{2 + 1} {x}^{2 + 1} - 3x[/tex]
[tex]\sf = \frac{2}{3} {x}^{3} - 3x[/tex]
[tex]\sf = \frac{2(3) {}^{3} }{3} - 3(3) - ( \frac{2(1) {}^{3} }{3} - 3(1))[/tex]
[tex]\sf = \frac{2(27)}{3 } - 9 - ( \frac{2}{3} - 3)[/tex]
[tex]\sf = \frac{54}{3} - 9 - ( - \frac{7}{3} )[/tex]
[tex]\sf = 9 - ( - \frac{7}{3} )[/tex]
[tex]\sf = 9 + \frac{7}{3} [/tex]
[tex]\sf = \frac{34}{3} [/tex]
[tex]\sf = 11 \frac{1}{3} \: satuan \: luas[/tex]
^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^
>> Detail Jawaban
Mapel : Matematika
Kelas : Xl
Materi : aplikasi integral
Bab : 8
Kode Soal : 2
kode kategorisasi : 12.2.8